Faktor-faktor yang Memengaruhi Kepemilikan Jaminan Kesehatan Pekerja Sektor Informal di Indonesia - Dodi Satriawan; Agus Joko Pitoyo; Sri Rum Giyarsih (TATALOKA, 2021)
Health investment has an important role in economic development and major capital in order to be able to do work. Lack of health insurance can be a poverty trap. This is the fundamental reason why health insurance receives the most attention in the SDG’s. Based on SAKERNAS data in 2017 the percentage of informal sector workers in Indonesia is still quite high, reaching 57.03 percent and of that number only 57.3 percent of informal sector workers have health insurance which means that almost half of the informal sector workers work without health insurance protection . This study aims to determine the factors that influence the ownership of health insurance for informal sector workers in Indonesia. The analysis was conducted inferentially using chi-square and binary logistic regression using SUSENAS data in March 2018. Based on the results of the analysis using chi-square obtained the results that all independent variables have a meaningful relationship with health insurance ownership so the analysis is continued with logistic regression. From the results of logistic regression it is found that the factors that influence the health insurance ownership of informal sector workers in Indonesia are the area of residence, marital status, status in the household, gender, age, NIK ownership, education level, business field, health complaints, status economics, and self-medication.